Pengaruh Hubungan Umur Tanaman Dengan Produktivitas Kopi Di Kelurahan Ledug Kecamatan Prigen Kabupaten Pasuruan - Hidayanti, Novi Itsna (Agrotechbiz : Jurnal Ilmiah Pertanian, 2023)
This research aims to determine the influence of the relationship between plant age and coffee productivity in Ledug sub-district, Prigen sub-district, Pasuruan regency, as well as a simple linear regression equation. The population of this research is coffee farmers in Ledug sub-district based on the number of Ledug coffee farmers which is 30 farmers for population problems in research that uses survey methods as data collection. The sample itself consisted of 30 people per farmer's tree. For the sample using the random sampling method. The analytical method used is a simple linear regression tool using Microsoft Word 2010 using a quantitative analysis model that analyzes the relationship between plant age and coffee productivity using the dependent variable Y and the independent variable X up to a and b constants. The research results show that the calculated t value 35 is >0.025 t table, so Ho is rejected, meaning there is an influence of plant age on productivity. So it is recommended that farmers harvest produce according to the age of the plants that are ready to harvest.